Subcellular localization of the coat protein in tobacco cells infected by cucumber mosaic virus isolated from Catharanthus roseus - Espinha, Luciana M. [UNESP]; Gaspar, José O. [UNESP] (My University, 1999)
Electron microscopy and immunolabelling with antiserum specific to cucumber mosaic virus coat protein were used to examine tobacco leaf cells infected by cucumber mosaic virus isolated from Catharanthus roseus (CMV-Cr). Crystalline and amorphous inclusions in the vacuoles were the most obvious cytological modifications seen. Immunogold labelling indicated that the crystalline inclusion was made up of virus particles and amorphous inclusions contained coat protein. Rows of CMV-Cr particles were found between membranes of dictyosomes, but membranous bodies and tonoplast-associated vesicles were not evident. Virus particles and/or free coat protein were easily detected in the cytoplasm by immunolabelling. No gold labelling was found within nuclei, chloroplasts and mitochondria.
Keywords: Capsid protein; Cucumovirus; Electron microscopy; Immunolabelling; Vinca rosea